Evaluation of Different Nitrogen Management on Yield and Some of the Yield Components of Rice (Shiroudi cultivar) (Baghdad Science Journal, 2020)
Nitrogen (N) is a key growth and yield-limiting factor in cultivated rice areas. This study has been conducted to evaluate the effects of different conditions of N application on rice yield and yield components (Shiroudi cultivar) in Babol (Mazandaran, Iran) during the 2015- 2016 season. A factorial experiment executed of a Randomized Complete Block Design (RCBD) used in three iterations. In the first factor, treatments were four N amounts (including 50, 90, 130, and 170 kg N ha-1), while in the second factor, the treatments consisted of four different fertilizer splitting methods, including T1:70 % at the basal stage + 30 % at the maximum tillering stage, T2:1/3 at the basal stage + 1/3 at the maximum tillering stage + 1/3 at the panicle initiation, T3: 25 % at the basal stage + 50 % at the maximum tillering stage + 25 % at the panicle initiation, and T4: 25 % at the basal stage + 25 % at the maximum tillering stage + 50 % at the panicle initiation. The results illustrate only the number of panicles (m2) which was significantly impacted by the year (at the CI of 0.99). Different levels of N had effects on the panicle length, the percentage of filled grain (PFG), whole grain in a plant, and yield (at the CI of 0.95). The panicle length, the PFG, and yield were also significantly affected by different methods of N splitting (at the P-v of 0.01). The interaction of N amount × N splitting had a significant effect on the panicle length, the PFG, and yield (at the CI of 0.95). In general, the most significant impact on the panicle length, the number of panicles (m2), the whole plant's grain, and yield observed after using 130 kg N ha-1. Besides, T3 showed the most notable effect on all the studied indices except for the panicle length.